An Accurate Battery Charger SEPIC-Coupled Inductor Using Fuzzy Type 2 - Putri, Berliana Rahma; Sudiharto, Indhana; Murdianto, Farid Dwi (Politeknik Negeri Ujung Pandang, 2021)
Recently, the needs of electrical energy have increased in line with the increasing population in Indonesia. Electrical in order to save the use of fossil energy, renewable is used, namely solar energy. Solar energy depends on the conditions of sunlight and the temperature of the solar panel. So, if the solar panel is directly connected to the battery, it will cause the battery be damaged. To overcome this, a controlled DC-DC converter is needed to stabilize the solar panel output before connecting to the battery. The DC-DC converter that used is a SEPIC coupled inductor converter, this converter has the ability to increase efficiency, the output polarity is not reversed, and avoid input current ripple. The control used to adjust the output of the SEPIC converter is a type 2 fuzzy logic controller because it has ability to find a set point value faster than other control logics and can handle uncertainty better than a type 1 fuzzy logic controller. The output of the SEPIC converter is used for charging lithium ion battery with a capacity 12V 21Ah. The output value of the SEPIC converter is 12.6V for charging voltage and 7A for charging current. The method used for battery charging is the constant current constant voltage method (cc-cv).